The Role of Financial Institutions in Promoting Sustainable Energy Practices for SMEs: A Strategic Approach - Verlinda Attipoe,; Ezinne C. Chukwuma-Eke,; Comfort Iyabode Lawal,; Solomon Christopher Friday,; Ngozi Joan Isibor,; Abiola Oyeronke Akintobi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The role of financial institutions in promoting sustainable energy practices for Small and Medium-sized Enterprises (SMEs) has become increasingly vital as the global transition to sustainable energy intensifies. This paper examines the strategic approach that financial institutions can take to support SMEs in adopting clean energy solutions, such as energy-efficient technologies and renewable energy. It discusses the financial barriers faced by SMEs, including high upfront costs, limited access to capital, and the lack of tailored financial products. Through an analysis of various financial tools—such as green bonds, sustainability-linked loans, venture capital, and blended finance models—this paper highlights how financial institutions can provide the necessary capital to empower SMEs to transition towards sustainable energy practices. Furthermore, the paper explores the role of risk mitigation strategies, capacity-building initiatives, and financial literacy programs as crucial components in overcoming these financial barriers. Finally, the paper emphasizes the importance of collaborative efforts between financial institutions, governments, and other stakeholders to create a favorable regulatory environment that incentivizes clean energy investments. By addressing these challenges and offering strategic solutions, financial institutions can significantly contribute to the widespread adoption of sustainable energy practices, thereby improving SMEs' environmental and economic sustainability. The study concludes with actionable insights for financial institutions, policymakers, and SMEs and recommendations for future research into emerging technologies and new financial models.
Keywords: Sustainable Energy Practices; Financial Institutions; SMEs; Green Finance; Clean Energy Financing; Risk Mitigation